Stabilized beta-catenin in thymic epithelial cells blocks thymus development and function. - Zuklys, S; Gill, J; Keller, M; Hauri-Hohl, M; Zhanybekova, S; Balciunaite, G; Na, K; Jeker, LT; Hafen, K; Tsukamoto, N; Amagai, T; Taketo, M; et al. (2009)
Thymic T cell development is dependent on a specialized epithelial microenvironment mainly composed of cortical and medullary thymic epithelial cells (TECs). The molecular programs governing the differentiation and maintenance of TECs remain largely unknown. Wnt signaling is central to the development and maintenance of several organ systems but a specific role of this pathway for thymus organogenesis has not yet been ascertained. In this report, we demonstrate that activation of the canonical Wnt signaling pathway by a stabilizing mutation of beta-catenin targeted exclusively to TECs changes the initial commitment of endodermal epithelia to a thymic cell fate. Consequently, the formation of a correctly composed and organized thymic microenvironment is prevented, thymic immigration of hematopoietic precursors is restricted, and intrathymic T cell differentiation is arrested at a very early developmental stage causing severe immunodeficiency. These results suggest that a precise regulation of canonical Wnt signaling in thymic epithelia is essential for normal thymus development and function.